The relationship between the job stressors and job performance in retail industry / Rasyima Ghazali and Siti Nor Asyikin Mohd Ramzan - Ghazali, Rasyima; Mohd Ramzan, Siti Nor Asyikin (2012)
Stress is a physiological response to any kind of demand, caused either by physically or emotionally or both. Job stress occurs when requirements do not match the employee's capabilities, resources and needs. Excessive job stress will contribute to adverse effect towards employees' performance. Poor leadership, poor communication, role ambiguity, workload and unpleasant work environment are the major job stressors that affect the employees' performance in retail industry. Therefore this paper is aimed to entail and explain the major job stressors faced by the employee in the retail industry setting. Quantitative paradigm will be used where distribution of questionnaires is proposed as method of study. The data gained will be analyzed using SPSS version 16.0. Excessive work stress is predicted to affect job performance and according to previous research findings, role ambiguity and work demand are predicted to be the most determining factors.